2018
DOI: 10.1007/s11356-018-1943-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a static magnetic field on biodegradation of wastewater compounds and bacteria recombination

Abstract: The current study presents results concerning the effect of a static magnetic field (SMF) on synthetic wastewater biodegradation by activated sludge and on dehydrogenase activity of microorganisms of activated sludge. The highest process efficiency was obtained for a SMF of 0.0075 T among the tested magnetic flux density values of 0.005-0.14 T. Decrease in COD was 25% higher for the bioreactor exposed to SMF compared with control experiments. The positive effect of SMF 0.0075-0.0080 T was confirmed in experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…These aspects have been investigated under different field strengths, static [42] and alternating magnetic fields as well as electromagnetic fields. Applications of magnetic treatment in biological processes span from biodegradation [37,[43][44][45][46] to bone healing [47] to production of biological active substances and chemicals. For the present work we consider the following mechanism to be relevant: the results by Buchachenko et al [48][49][50][51], which show that magnetic fields can accelerate ATP production by changing the spin-state of the compo-nents involved, similar to Coey's considerations concerning the effect of magnetic gradients on proton spin states on the surface of DOLLOPs [21], and the hypothesis by Liboff [52], according to which ion-cyclotron resonance in living cells can facilitate the transport of Ca 2+ through cell membranes.…”
Section: Direct Effects Of Magnetism On Organisms and Biochemical Reactionsmentioning
confidence: 99%
“…These aspects have been investigated under different field strengths, static [42] and alternating magnetic fields as well as electromagnetic fields. Applications of magnetic treatment in biological processes span from biodegradation [37,[43][44][45][46] to bone healing [47] to production of biological active substances and chemicals. For the present work we consider the following mechanism to be relevant: the results by Buchachenko et al [48][49][50][51], which show that magnetic fields can accelerate ATP production by changing the spin-state of the compo-nents involved, similar to Coey's considerations concerning the effect of magnetic gradients on proton spin states on the surface of DOLLOPs [21], and the hypothesis by Liboff [52], according to which ion-cyclotron resonance in living cells can facilitate the transport of Ca 2+ through cell membranes.…”
Section: Direct Effects Of Magnetism On Organisms and Biochemical Reactionsmentioning
confidence: 99%
“…84 Possible mechanisms of magnetic elds on living organisms include the impact on cell membranes and transmembrane signals, the impact on microbial genes, and the impact on cellular enzyme activity. 85 The magnetic biological effect is generally applied to the microbial treatment of wastewater in which the activity of functional microorganisms is strengthened by the magnetic eld treatment, and the microorganisms in the sludge possess a stronger adsorption and utilization ability relative to the organic matrix in wastewater, so that the biological purication efficiency of the wastewater is improved. 86 In a BES, this process may affect the activity of enzymes and the bioelectrochemical activity or biomass of biolms and thus exert an inuence on the organizational structure of microorganisms.…”
Section: Magnetic Eldmentioning
confidence: 99%
“…The Gram-negative E. coli was found to be more sensitive to SMF than the Gram-positive species S. epidermidis [ 16 ]. In some cases, the inhibition of bacterial growth by SMF was restricted within a certain time window during experimentation, called the biological window effect [ 17 ]. On the other hand, Potenza et al (2004) reported that E. coli grew significantly faster in 300 mT SMF than in GMF when cultured in the modified liquid Luria–Bertani (LB) medium with 6 g/L glutamic acid and 4.5 g/L NaCl, whereas no magnetic effect was observed when the traditional LB medium was used [ 18 ].…”
Section: Introductionmentioning
confidence: 99%